( | 3 | x | + | 1 | ) | ( | x | − | 1 | ) | = | ( | 4 | x | − | 1 | ) | ( | x | − | 1 | ) |
Left side of the equation = | 3 | x | ( | x | − | 1 | ) | + | 1 | ( | x | − | 1 | ) |
= | 3 | x | x | − | 3 | x | × | 1 | + | 1 | ( | x | − | 1 | ) |
= | 3 | x | x | − | 3 | x | + | 1 | ( | x | − | 1 | ) |
= | 3 | x | x | − | 3 | x | + | 1 | x | − | 1 | × | 1 |
= | 3 | x | x | − | 3 | x | + | 1 | x | − | 1 |
= | 3 | x | x | − | 2 | x | − | 1 |
3 | x | x | − | 2 | x | − | 1 | = | ( | 4 | x | − | 1 | ) | ( | x | − | 1 | ) |
Right side of the equation = | 4 | x | ( | x | − | 1 | ) | − | 1 | ( | x | − | 1 | ) |
= | 4 | x | x | − | 4 | x | × | 1 | − | 1 | ( | x | − | 1 | ) |
= | 4 | x | x | − | 4 | x | − | 1 | ( | x | − | 1 | ) |
= | 4 | x | x | − | 4 | x | − | 1 | x | + | 1 | × | 1 |
= | 4 | x | x | − | 4 | x | − | 1 | x | + | 1 |
= | 4 | x | x | − | 5 | x | + | 1 |
3 | x | x | − | 2 | x | − | 1 | = | 4 | x | x | − | 5 | x | + | 1 |